PRACTICAL ASPECTS FOR STOCK MARKET DEVELOPMENT (World Economics and Finance Bulletin, 2022)
The article reflects the practical aspects of stock exchanges and their development. Separately reflected the situation in the global stock market. In conclusion, assumptions are made for the near future.
Keywords: Stock exchange; securities market; market functions; infrastructure